2002
DOI: 10.1074/jbc.m105232200
|View full text |Cite
|
Sign up to set email alerts
|

Folding of a de Novo Designed Native-like Four-helix Bundle Protein

Abstract: The folding of a model native-like dimeric four-helix bundle protein, (␣ 2 ) 2 , was investigated using guanidine hydrochloride, hydrostatic pressure, and low temperature. Unfolding by guanidine hydrochloride followed by circular dichroism and intrinsic fluorescence spectroscopy revealed a highly cooperative transition between the native-like and unfolded states, with free energy of unfolding determined from CD data, ⌬G unf ‫؍‬ 14.3 ؎ 0.8 kcal/mol. However, CD and intrinsic fluorescence data were not superimpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
2

Year Published

2003
2003
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 28 publications
2
28
0
2
Order By: Relevance
“…Thus, the most likely interpretation is that binding of bis-ANS occurred to a hydrophobic region located somewhere close to the active site but that this region is separate from the region engaged in binding of LPL to the lipid/ water interface of emulsified substrates. (47)(48)(49). In some cases bis-ANS may interact with specialized ligand-binding regions of native proteins.…”
Section: Studies Of the Complexes Of Bis-ans With Lpl By Circularmentioning
confidence: 99%
“…Thus, the most likely interpretation is that binding of bis-ANS occurred to a hydrophobic region located somewhere close to the active site but that this region is separate from the region engaged in binding of LPL to the lipid/ water interface of emulsified substrates. (47)(48)(49). In some cases bis-ANS may interact with specialized ligand-binding regions of native proteins.…”
Section: Studies Of the Complexes Of Bis-ans With Lpl By Circularmentioning
confidence: 99%
“…The band intensity of the turn structure seems to slightly decrease as pressure increases. Recently, Chapeaurouge et al 20 reported the pressure-induced unfolding of ( 2 ) 2 four-helix bundle protein, which has nearly the same primary structure constructing the hydrophobic core of (-l-) 2 , using the spectral center of mass of Trp fluorescence. They concluded that the pressure of about 350 MPa induces reversible dissociation of dimmer of ( 2 ) 2 to partially folded monomer.…”
mentioning
confidence: 99%
“…30 and 31) and de novo designed proteins (7,14,32). Hydrophobic interactions, which are believed to be the major stabilizing forces of protein cores, are destabilized at low temperatures, leading to protein unfolding (33).…”
Section: Discussionmentioning
confidence: 99%